The protection of the right of women under the African human rights system in light of the HIV/AIDS pandemic: a case study of Mozambique - De Amaral, Leopoldo (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.